Correlations among learning strategy, learning motivation, and speaking ability of students in junior high school - Lismiyati, Lismiyati; Simaibang, Baginda; Mulyadi, Mulyadi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This thesis is concerned with the inquiry on the correlations among learning strategy, learning motivation and the seventh grade students’ speaking ability of SMP Negeri 03 Muaradua OKUS. The problem of this study is to investigate the correlations among learning strategy, learning motivation and speaking ability. The total number of the population was 76 students. The sample for this study was 52 students taken through cluster random sampling technique. Data were collected by adopting questionnaire for learning strategy and learning motivation, and a test for speaking ability. Data were analyzed by using r-product moment and multiple regression. Findings show that there are significant correlations among learning strategy, learning motivation, and speaking ability. Conclusions suggest that learning strategy and learning motivation have significant correlations with speaking ability.